2022
DOI: 10.1039/d2ra02745c
|View full text |Cite
|
Sign up to set email alerts
|

Facile production of quercetin nanoparticles using 3D printed centrifugal flow reactors

Abstract: A 3D printed reactor-in-a-centrifuge (RIAC) was developed to produce drug nanocrystals. Quercetin nanocrystals were manufactured at varying operational and formulation conditions, and had a small size (190–302 nm) and low size dispersity (PDI < 0.1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Importantly, the transition temperature of a lipid (i.e., the temperature at which the lipid transitions from the ordered gel phase to the disordered liquid crystalline phase) determines the rigidity of a lipid bilayer and can impact the physical properties and stability of the formed liposomes [34]. Moreover, liposomal formulations investigated in previous research often In previous research, we showed that the RIAC is capable of producing liposomes (as well as inorganic nanoparticles and drug nanocrystals) at a relatively low cost and without requiring specialist instrumentation [25,30]. These earlier proof-of-concept studies, however, employed model lipids that are less commonly used clinically for therapeutic purposes [31,32].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the transition temperature of a lipid (i.e., the temperature at which the lipid transitions from the ordered gel phase to the disordered liquid crystalline phase) determines the rigidity of a lipid bilayer and can impact the physical properties and stability of the formed liposomes [34]. Moreover, liposomal formulations investigated in previous research often In previous research, we showed that the RIAC is capable of producing liposomes (as well as inorganic nanoparticles and drug nanocrystals) at a relatively low cost and without requiring specialist instrumentation [25,30]. These earlier proof-of-concept studies, however, employed model lipids that are less commonly used clinically for therapeutic purposes [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, we showed that the RIAC is capable of producing liposomes (as well as inorganic nanoparticles and drug nanocrystals) at a relatively low cost and without requiring specialist instrumentation [ 25 , 30 ]. These earlier proof-of-concept studies, however, employed model lipids that are less commonly used clinically for therapeutic purposes [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation